PENGGUNAAN MODEL PEMBELAJARAN FLIPPED CLASSROOM UNTUK PEMBELAJARAN DARING SOSIOLOGI DI MASA PANDEMI COVID-19 KELAS X.IPS SMA NEGERI 1 JUWANA KAB. PATI TAHUN 2020 - Suharno, Suharno (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2020)
Government policies to implement online learning during the covid pandemic 19 caused many problems in schools; that is, lack of effectiveness on learning communication, students boredom, too much teacher assignments, and complaints about quota and internet networks. In this emergency situation, teachers must act quickly so that learning can run effectively. The cell phone which was originally only used as a communication media, has now become multifunctional. It is now used to provide learning material and assignments in a very short duration. The flipped classroom learning model is learning that combines learning in the classroom with learning outside the classroom with the aim of maximizing learning activities. Learning activities that are usually done in class, are now done at home. The problem in this study is